Old Age and its Negative Impact on Oral Health Status - Radha Prasanna Dalai1 , Sourav Chandra Bidyasagar Bal1 , Subrat Padhihari2 , Sashikant Sethi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The older group of people (above sixty-five years) are facing lots of health and oral health issues due to thephenomenon of getting old. For that reason, this group needs the most attention to their health. Towards theend of the 20th century, the configuration of various age groups of people transformed tremendously. Thereare more older people and much more entered into the older group. This dynamic change has a direct effecton oral and systemic health. Dentist has great hand in solving the oral problem in geriatric people. Dentistshould always consider the nutrition factor of geriatric patients. Topmost problem regarding the oral carefacility in the older population is underestimated the oral disease Proper dentist population ratio throughoutour nation to provide better dental care. Regular screen camps in different places to find older patients andgave them special care because due to rapid dental caries, periodontal disease, tooth loss the old peoplefacing various problems.